Community-based survey during rabies outbreaks in Rangjung town, Trashigang, eastern Bhutan, 2016 - Tenzin, Tenzin (BMC Infect Dis, 2017)
BACKGROUND: Rabies is a highly fatal disease transmitted through the bite of a rabid animal. Human deaths can be prevented by prompt administering of rabies vaccine and rabies immunoglobulin following the exposure. An assessment of community knowledge, awareness and practices on rabies is important during outbreak to understand their preparedness and target educational messages and response activities by the rapid response team. METHODS: A rabies outbreak has occurred in Rangjung town, eastern Bhutan on 4 October 2016. A rapid response team was activated to investigate outbreak and to establish a control program. A community-based questionnaire survey was conducted from 20 to 21 October 2016 to assess the community knowledge of rabies to guide outbreak preparedness and also target educational messages and response activities by the RRT. RESULTS: A total of 67 respondents were interviewed, of which 61% were female and 39% male. All the respondents have heard of rabies (100%), have knowledge on source of rabies (dog) and its mode of transmission in animals and humans. Most (61%) respondents were aware and also indicated that they would wash the animal bite wound with soap and water and seek medical care on the same day of exposure (100%). Majority (94%) of the respondents have indicated that they would report to the government agencies if they see any suspected rabid dogs in the community and suggested various control measures for dog population management and rabies in Rangjung including neutering procedure and mass dog vaccination. Although only few (10%) of the respondents households owned dogs and cats, but 50% of them have indicated that their dogs were allowed to roam outside the home premises posing risk of contracting rabies through rabid dog bites. CONCLUSIONS: Although this study indicates a high level of knowledge and awareness on rabies among the community, there exists some knowledge gaps about rabies and therefore, an awareness education should be focused on the source of rabies and rabies virus transmission route to reduce public concern on nonexposure events thereby reducing the cost on unnecessary postexposure treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-017-2393-x) contains supplementary material, which is available to authorized users.